A new predaceous midge of the Palpomya tibialis group from northeastern Argentina (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2006)
Palpomyia iberaensis n. sp., was collected by Malaise trap in the province of Corrientes, Argentina and its female and attached male genitalia are described and illustrated. The species is distinguished by the following combination of characters: females with dark brown legs except fore trochanter, basal 1/2 of fore femur, basal 2/3 of mid femur, fore and mid tibiae except extreme tip, yellowish brown; fore femur with four to five, mid femur with two ventral spines; abdomen lacking gland rods. Males with gonocoxite stout, with a conspicuous posteromesal pointed hook; gonostylus short, curved; parameres entirely divided, the distal portions slender with two posteriorly directed processes. This species is placed in the tibialis group in spite of the curious parameres without recurved tips. The species is compared with its congener Palpomyia mellichroa, from southeastern Brazil.